On the Comparison of Markov Chains-based Models in Process Mining for Healthcare: A Case Study - Mauro Vallati; Stefania Orini; Mariagrazia Lorusso; Mariachiara Savino; Roberto Gatta; Massimiliano Filosto (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
In the last decade, Process Mining has become a significant field to help healthcare process experts understand and gain relevant insights about the processes they execute. One of the most challenging questions in Process Mining, and particularly in healthcare, typically is: how good are the discovered models? Previous studies have suggested approaches for comparing the (few) available discovery algorithms and measure their quality. However, a general and clear comparison framework is missing, and none of the analyzed algorithms exploits Markov Chains-based Models.